Petrological Studies of the Yamato Meteorites Part1. Mineralogy of the Yamato Meteorites - Okada, Akihiko (1975)
P(論文) In 1969,the 10th Japanese Antarctic Research Expedition Team collected nine stones lying on the glacier in the southeastern area of the Yamato Mountains, Antarctica (70°S, 37°E). By the mass-spectrometric study of rare gas and the chemical analysis of the stones, SHIMA, SHIMA and HINTENBERGER (1973) found four of them to be meteorites, and named them the Yamato (a), Yamato (b), Yamato (c) and Yamato (d). The other five stones were also determined to be meteorites because of their chondritic structures, and were named the Yamato (e), Yamato (f), Yamato (g), Yamato (h) and Yamato (i). According to the chemical composition, the Yamato (a), Yamato (b), Yamato (c) and Yamato (d) were assigned to an enstatite chondrite, a calcium-poor achondrite, a type III carbonaceous chondrite and a high-iron group chondrite, respectively. In this work, the mineralogical properties of the Yamato (a), Yamato (b), Yamato (c), Yamato (d) and Yamato (g) were studied in detail. The texture of meteorites and the occurrence, content and optical property of minerals were optically investigated with the polarizing microscopy in both the transmitted and the reflected light. Chemical compositions of main silicate minerals, olivine and pyroxene, and the silica minerals of the Yamato (a), Yamato (b) and Yamato (c) were analyzed with the electron probe microanalyzer. departmental bulletin paper